2019
DOI: 10.1136/bmjebm-2019-111207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial registry use in minimally invasive surgical oncology systematic reviews and meta-analyses

Abstract: Publication bias can arise in systematic reviews when unpublished data are omitted and lead to inaccurate clinical decision making and adverse clinical outcomes. By conducting searches of clinical trial registries (CTRs), researchers can create more accurate systematic reviews and mitigate the risk of publication bias. The aims of this study are: to evaluate CTR use in systematic reviews and meta-analyses within the minimally invasive surgical oncology (MISO) literature; to conduct a search of ClinicalTrials.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Our findings also agree with two studies which examined the number of trials identified via http://clinialtrials.gov for systematic reviews of surgical interventions 12,14 . Fuller et al found additional eligible trials for 64% (16/25) of the reviews, 12 while Reddy et al found additional eligible studies for 59% (59/100) of reviews 14 .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings also agree with two studies which examined the number of trials identified via http://clinialtrials.gov for systematic reviews of surgical interventions 12,14 . Fuller et al found additional eligible trials for 64% (16/25) of the reviews, 12 while Reddy et al found additional eligible studies for 59% (59/100) of reviews 14 .…”
Section: Discussionsupporting
confidence: 90%
“…[7][8][9][10][11][13][14][15][16]24 Our findings also agree with two studies which examined the number of trials identified via ClinialTrials.gov for systematic reviews of surgical interventions. 12,14 Fuller et al found additional eligible trials for 64% (16/ 25) of the reviews, 12 while Reddy et al found additional eligible studies for 59% (59/100) of reviews. 14 Similarly, we identified additional trials for 60% (15/25) of the reviews of surgical interventions included in our study from different surgical subspecialities; mostly from orthopaedics surgery, followed by general surgery, neurosurgery, and bariatric surgery.…”
Section: Comparing To Other Studiesmentioning
confidence: 99%
See 3 more Smart Citations